2009
DOI: 10.3989/ajbm.2225
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species and species pairs in lichens: A discussion on the relationship between molecular phylogenies and morphological characters

Abstract: ResumenCrespo, A. & Pérez-Ortega, S. 2009. Especies crípticas y pares de especies en líquenes: una discusión sobre la relación entre la filogenia molecular y los caracteres morfológicos. Anales Jard. Bot. Madrid 66S1: 71-81 (en inglés).Como en otras disciplinas, el impacto producido por la filogenia molecular en el conocimiento de los hongos liquenizados ha producido avances y cambios conceptuales importantes. Esto ha sido especialmente cierto en la sistemática y ha afectado de una manera muy notable en aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 72 publications
6
104
0
2
Order By: Relevance
“…Traditional taxonomic treatments within the family largely rely on chemistry, apothecium shape, and ascospore morphology (Staiger 2002). Molecular data on other lichenized fungal lineages have shown that the classification based on these characters usually underestimates the number of distinct lineages under a single taxonomic name (Crespo and Lumbsch 2010;Crespo and Ortega 2009;Hodkinson and Lendemer 2011;McCune and Schoch 2009;Ruprecht et al 2010;Spribille et al 2011;Vondrák 2012;Wedin et al 2009). Within Graphidaceae, traits traditionally used for classification were shown to have evolved independently several times (Lumbsch et al 2014;Rivas Plata and Lumbsch 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Traditional taxonomic treatments within the family largely rely on chemistry, apothecium shape, and ascospore morphology (Staiger 2002). Molecular data on other lichenized fungal lineages have shown that the classification based on these characters usually underestimates the number of distinct lineages under a single taxonomic name (Crespo and Lumbsch 2010;Crespo and Ortega 2009;Hodkinson and Lendemer 2011;McCune and Schoch 2009;Ruprecht et al 2010;Spribille et al 2011;Vondrák 2012;Wedin et al 2009). Within Graphidaceae, traits traditionally used for classification were shown to have evolved independently several times (Lumbsch et al 2014;Rivas Plata and Lumbsch 2011).…”
Section: Introductionmentioning
confidence: 97%
“…The topic of cryptic species, cases where two or more distinct species-level lineages are erroneously classified (and hidden) under one nominal taxon (Bickford et al 2007), has been frequently reviewed for lichen-forming fungi (Lumbsch and Leavitt 2011;Crespo and Lumbsch 2010;Crespo and Pérez-Ortega 2009;Printzen 2009). Although novel diagnostic phenotypic characters may potentially be identified corroborating "cryptic" species, these previously unrecognized lineages generally remain difficult to classify within a traditional phenotype-based taxonomy (Leavitt et al 2013c, d).…”
Section: Species In Lichenized Fungimentioning
confidence: 99%
“…This is because, apparently, database of lichens are far from complete and, therefore molecular identifications, are in some cases incorrect. Crespo and Pérez-Ortega (2009) reported that there is a lack of correlation between phylogenetic and morphological data, at least for characters normally used in lichen systematics. Table 4 Chlorophyll a values (mean of triplicates) obtained by spectro-fluorescence and by extraction method for AC mortar after inoculation, after incubation and after the application of the biocides.…”
Section: Discussionmentioning
confidence: 99%